Regulations, securitisation and the financing of airport infrastructure in Sub-Saharan Africa: a case study - Dlamini, Phumzile Zimasa (My University, 2017)
It is well acknowledged that infrastructure provision is linked to economic growth , in particular airports are viewed a strategic catalysts to this growth bringing about increased opportunities for trade, tourism, and serving as an enabler for business. African airports have historically suffered underinvestment as a result of competing priorities for government funding; growing safety concerns, increased traffic growth and globalisation, and the need for refurbishment and modernisation of systems. African nations are now beginning to spend considerable amounts on aviation infrastructure. The purpose of this study evaluate the financing mechanisms available to governments, to access the role that airport economic regulation plays in attracting investment and the potential of leveraging the securitisation model for the financing of aviation infrastructure. It was found that, no one funding mechanism is king and that airport owners and operators should attempt a diversification strategy towards their funding sources, taking into account that the investment appetite of various investors will be different at the various phases of infrastructure project delivery. It was found that airport regulation is key to harnessing the certainly of future cash flows required by private investors , and may be the required mechanism to off load the financial burden of smaller airports from the government budgets. Lastly it was found that development finance institutions may be the biggest benefactors to utilising the securitisation model to unlock further developmental funding; key to this is the support of institutional investors.
A project report submitted in partial fulfilment of the requirements for the degree of Masters of Management (Finance and Investment) in the Faculty of Commerce, Law and Management Wits Business School, University of the Witwatersrand, 2016
Keywords: Airports--Africa, Sub-Saharan; Economic development--Africa, Sub-Saharan; Infrastructure (Economics)